(untitled) (Raparin Journal of Humanities (RJH), 2024)
An increase in the population and its needs, the development of transportation means and the diversification of transportation networks, as well as the differences in the geographical location of the population, are reasons for paying more attention to the road and transportation sector. In addition to all this, the increase in traffic accidents at the local and global levels is another reason for the attention of different fields. Pishdar district, as a geographical unit in the Kurdistan Region, has seen significant progress in the field of transportation in recent years, which has caused it to have its share of traffic accidents. The main goal of this study is to identify the characteristics of road networks in Pishdar district as well as a geographical analysis of traffic accidents and determine the level of solving these problems that are observed in the district in a scientific way. The research plan is divided into three main parts, each of which consists of two main sections: Part 1. This part describes the characteristics of transport networks and consists of two main sections. The first section includes the classification of road networks, and the second section includes the distribution of road networks at the level of administrative units in the study area. Part 2. This part is dedicated to the role of geographical principles in the time and place of traffic accidents in Pishdar district. The first is about the difference in time according to (month and year), and the second is the difference in location according to (city and outside the city). Part 3. This part is dedicated to how the most significant natural factors, which also include the most significant human factors, affect traffic accidents.